The Curse of Knowledge in Reasoning About False Beliefs - Birch, Susan A.J.; Bloom, Paul (Psychological Science, 2007)
Assessing what other people know and believe is critical for accurately understanding human action. Young children find it difficult to reason about false beliefs (i.e., beliefs that conflict with reality). The source of this difficulty is a matter of considerable debate. Here we show that if sensitive-enough measures are used, adults show deficits in a false-belief task similar to one used with young children. In particular, we show a curse-of-knowledge bias in false-belief reasoning. That is, adults' own knowledge of an event's outcome can compromise their ability to reason about another person's beliefs about that event. We also found that adults'perception of the plausibility of an event mediates the extent of this bias. These findings shed light on the factors involved in false-belief reasoning and are discussed in light of their implications for both adults' and children's social cognition.